2008
DOI: 10.2134/jeq2007.0360
|View full text |Cite
|
Sign up to set email alerts
|

Watershed Vulnerability Predictions for the Ozarks Using Landscape Models

Abstract: Forty-six broad-scale landscape metrics derived from commonly used landscape metrics were used to develop potential indicators of total phosphorus (TP) concentration, total ammonia (TA) concentration, and Escherichia coli bacteria count among 244 sub-watersheds of the Upper White River (Ozark Mountains, USA). Indicator models were developed by correlating field-based water quality measurements and contemporaneous remote-sensing-based ecological metrics using partial least squares (PLS) analyses. The TP PLS mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 18 publications
1
13
0
5
Order By: Relevance
“…In addition, multiple response variables can be included in the same PLS model. Generally, VIP scores above 1.0 suggest that a variable is important (Fraterrigo andDowning 2008, Mehmood et al 2012), but variables with scores slightly below 1.0 might be marginally important (Lopez et al 2008, Monk et al 2013. To assess the sensitivity of our inferences to ignoring this spatial structure, we compared PLS regression to a mixed modeling approach that explicitly accounted for the hierarchical data structure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multiple response variables can be included in the same PLS model. Generally, VIP scores above 1.0 suggest that a variable is important (Fraterrigo andDowning 2008, Mehmood et al 2012), but variables with scores slightly below 1.0 might be marginally important (Lopez et al 2008, Monk et al 2013. To assess the sensitivity of our inferences to ignoring this spatial structure, we compared PLS regression to a mixed modeling approach that explicitly accounted for the hierarchical data structure.…”
Section: Discussionmentioning
confidence: 99%
“…Forest is mostly associated with low water pollution in various studies of watersheds around the world (Osborne and Kovacic, 1993;Sliva and Williams, 2001;Novotny, 2002;Bahar et al, 2008;Lopez et al, 2008;Huang et al, 2014). Based on OLS, some studies find no significant correlations between forest land and water pollution (Sponseller et al, 2001;Tran et al, 2010;Huang et al, 2013a).…”
Section: Effect Of Forest Land On Water Pollutionmentioning
confidence: 99%
“…Generally, built-up land and agricultural land have significant positive correlations with water pollution, which are associated with point or non-point source pollution (Johnson et al, 1997;Sliva and Williams, 2001;Fedorko et al, 2005;Mehaffey et al, 2005;Stutter et al, 2007;Tu et al, 2007;Bahar et al, 2008;Tran et al, 2010;Pratt and Chang, 2012;Yang, 2012). Woodland is significantly negatively correlated with nutrients, due to the general understanding that forests can absorb nutrients (Osborne and Kovacic, 1993;Novotny, 2002;Galbraith and Burns, 2007;Bahar et al, 2008;Lopez et al, 2008). However, the relationships between land use and water pollution can be inconsistent across time and space.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have linked stream pollutants to land use variables using process-based hydrological models (Jha et al, 2010;Kirsch et al, 2002;Ullrich and Volk, 2009) or statistical methods (Lenat and Crawford, 1994;Liu et al, 2009;Lopez et al, 2008;Mehaffey et al, 2005;Nash et al, 2009). Process based hydrologic models have been successfully used to characterize watershed processes and sources of stream pollutants; however these models require detailed input data, which may not be available for some areas.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kirsch et al (2002) showed the difficulty of calibrating a SWAT model for Rock River basin in Wisconsin, due to limited data for numerous lakes, reservoirs and dams in the basin. Using statistical regression methods, agricultural land was found to be a major contributor to nutrients in Oregon, New York, and the Missouri-Arkansas Ozark region (Lopez et al, 2008;Mehaffey et al, 2005;Nash et al, 2009). In addition, Liu et al (2009) found that urban and agricultural lands contribute many pollutants (such as TP, bacteria, metals, low dissolved oxygen, alkalinity and conductivity) to Wisconsin streams using similar statistical methods.…”
Section: Introductionmentioning
confidence: 99%